Comparative efficacy of azadirachtin on the larval population of culex quinquefasciatus, anopheles stephensi, and aedes aegypti (diptera: culicidae) in gujarat, india. - M.S.Shivakumar; Ruchika Kataria (International Journal of Pharma and Bio Sciences, 2010)
In the present study, the larvicidal action of Azadirachtin was tested on 4th Instar larvae of Anopheles stephensi, Culex quinquefasciatus and Aedes aegypti. Graduated concentrations of Azadirachtin at 1, 3, 5, 10, 15 and 30 ppm were tested as per WHOPES protocol for larvicidal efficacy. Results indicate that Culex larvae require a higher concentration of 30ppm for 100% larval mortality whereas for Aedes it is 10ppm. In Anopheles 100% mortality was recorded at 3ppm. LC99 estimates suggest that An.stephensi is highly susceptible to the Azadirachtin as compared to Cx.quinquefasciatus and Ae.aegypti.